ANALISA PRODUKTIVITAS EXCAVATOR KOMATSU PC 2000 PADA OVERBURDER REMOVAL DI PT. JHONLIN BARATAMA - Heldayanti; I Wayan Wawan Mariki; Duan Arpilanoor (Scientific Journal of Mechanical Engineering Kinematika, 2021)
In mining activities, one of the overburden activities is heavy equipment working at PT. Jhonlin Baratama in digging and loading using a PC 2000 excavator for the productivity process. With the company's production target of 865 BCM/hour. This research aims to determine the data of the cycle time in the excavator productivity of the excavator PC 2000 by using the calculation method match factor. The results of the calculation of the total average cycle time of the excavator is PC 200030.33 seconds, with a Bucket capacity of 12 BCM, Fill factor 0.9%, Swell Factor 0.8 with efficiency work 0.79%, while the total average HDK conveyance is Komatsu 78510.61 seconds and HDK Komatsu 465 is 9.99 minutes, from the calculation of the productivity of the excavator PC 2000 of 810 BCM/hour so that the production target has not been achieved optimally because in processing the macth factor is 0.74.